Consensus by High Gegree of DeGroot model for multi-agent systems - Rawad, Abdulghafor; sharyar, Wani; Hassan, Raini; Ismail, Amelia Ritahani (2020)
Nonlinear distributions by the high degree of DeGroot model has been studied in this for consensus problem of multi-agent systems (MAS). The idea behind the convergence of nonlinear distribution is that when the degree of nonlinear distribution is increasing the number of iterations is in turn decreasing. From these viewpoints, the efficient aspects of the proposed nonlinearity model by high degree are that the resulting process is of fast convergence and the consensus could not depend on the kind of transition matrix